Implementation of the child labour policy in South Africa - Asobo, Simo Mambi (My University, 2016)
Child labour is a social problem that affects several countries worldwide, and South Africa is not an exception. It is the result of adverse economic conditions in the country, where children feel they have to resort to finding employment in order to support their families. There is a general consensus that child labour in South Africa needs to be dealt with, and this is seen via the ratification of the two most important ILO conventions that speak to child labour. The ratification of these conventions led to the development of a child labour policy for South Africa; the Child Labour Programme of Action. However, despite the existence of this policy and its implementation, child labour continues. This report looked at how the child labour policy was implemented, and to verify if the continued occurrence of child labour was due to a disconnection between the policy as it is presented on paper, and those who are supposed to implement the policy on the ground. The report used qualitative methods, specifically documentary analysis and interviews. The documents that were analysed included the Child Labour Programme of Action, as well as its follow up documents. Meanwhile, government officials as well as members of civil society were the interview subjects. The main finding of the research is that the implementers of the policy do not have a full understanding of the policy and what it entails. And because of this they are unable to properly implement the policy to produce an effective solution against child labour. The report concludes with recommendations intended to help the government to get more out of the Child Labour Programme of Action.
A research report submitted to the Faculty of Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in the field of Public Policy) , April 2016
Keywords: Child labor--South Africa; Child labor--Government policy--South Africa; Child labor--Law and legislation--South Africa; South Africa--Economic policy